An Analysis of The Effect of Fashion Consciousness as A Mediating Factor on Hijab Fashion Consumption in Indonesia - Mayangsari Edastami; Miyasto -; Akhmad Affandi Mahfudz (Institute for Research and Community Empowerment (LPPM TAZKIA), 2019)
This research aims to analyze the influence factors in fashion consciousness on consumers in Indonesia, especially in relation to consumption of hijab-fashion. This matter is affected by the increasing of halal fashion industry in the world. Beside that, Indonesia is a country with large number of consumption in Hijab-fashion industry. So it is important to know about the contribution of aspects of fashion consciousness to the interest of these onsumen in consuming hijab-fashion. This study focus to the factors that influence fashion consciousness and consumption of hijab-fashion in Indonesia. These factors are religiosity, dressing style, source of knowledge, fashion motivation, and uniqueness also tha fashion consciousness as a intervening variable. This study use a structural equation model by analyzing the facts that have occurred. In this study, the primary data was collected using questionaire with a total of 483 respondents. In this study the first interesting finding was that religiosity has a negative effect to hijab fashion consciousness. Furthermore, there is a positive significant influence on dressing style and fashion motivation in fashion consciousness, but there is no significant influence on the source of knowledge and the uniqueness in the fashion consciousness. This study also found that fashion consciousness has a significant effect on the consumption of hijab-fashion in Indonesia. By looking at the results of this study, it is hoped that it can be useful especially for hijab-fashion manufacturers and industru in Indonesia in considering a more effective strategy in attracting the attention of Muslim consumers in Indonesia. Producers are expected to be able to provide the consumer expectations, especially for religious consumers. Because religious consumers will be more critical in decision related to the selection of fashion models and consumption of hijab-fashion. Thus, producers must provide fashionable product innovations in accordance with the criteria and regulations stipulated in the Islamic religion. So that religious consumers feel comfortable in consuming the modest of hijab-fashion.